Trends and determinants of stillbirth in developing countries: results from the Global Network's Population-Based Birth Registry - Sarah Saleem; Shiyam Sunder Tikmani; Elizabeth M. McClure; Janet L. Moore; Syed Iqbal Azam; Sangappa M. Dhaded; Shivaprasad S. Goudar; Ana Garces; Lester Figueroa; Irene Marete; Constance Tenge; Fabian Esamai; et al. (BMC, 2018)
Abstract Background Stillbirth rates remain high, especially in low and middle-income countries, where rates are 25 per 1000, ten-fold higher than in high-income countries. The United Nations' Every Newborn Action Plan has set a goal of 12 stillbirths per 1000 births by 2030 for all countries. Methods From a population-based pregnancy outcome registry, including data from 2010 to 2016 from two sites each in Africa (Zambia and Kenya) and India (Nagpur and Belagavi), as well as sites in Pakistan and Guatemala, we evaluated the stillbirth rates and rates of annual decline as well as risk factors for 427,111 births of which 12,181 were stillbirths. Results The mean stillbirth rates for the sites were 21.3 per 1000 births for Africa, 25.3 per 1000 births for India, 56.9 per 1000 births for Pakistan and 19.9 per 1000 births for Guatemala. From 2010 to 2016, across all sites, the mean stillbirth rate declined from 31.7 per 1000 births to 26.4 per 1000 births for an average annual decline of 3.0%. Risk factors for stillbirth were similar across the sites and included maternal age < 20 years and age > 35 years. Compared to parity 1-2, zero parity and parity > 3 were both associated with increased stillbirth risk and compared to women with any prenatal care, women with no prenatal care had significantly increased risk of stillbirth in all sites. Conclusions At the current rates of decline, stillbirth rates in these sites will not reach the Every Newborn Action Plan goal of 12 per 1000 births by 2030. More attention to the risk factors and treating the causes of stillbirths will be required to reach the Every Newborn Action Plan goal of stillbirth reduction. Trial registration NCT01073475.